EFEKTIVITAS PENGGUNAAN LEMBAR KERJA PESERTA DIDIK BERBASIS PENDEKATAN SAINTIFIK TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VI SDN NO. 84 GANRANG-GANRANG KABUPATEN JENEPONTO - Putri, Nengsih Ayu; Usman; Nur, Fitriani (Prodi PGMI IAI Sahid, 2024)
This study aims to determine the learning outcomes of students before and after using LKPD. This research is a quasi-experimental research, with a quasi-experimental design. The population in this study consisted of two classes, namely class VI/a and VI/b with a total of 44 students at SDN No. 84 Ganrang-ganrang, Jeneponto Regency. The sample technique used was saturated sample, so that class VI/a with a total of 22 students was selected as the experimental class and class VI/b with a total of 22 students as the control class. The results of the analysis show that the average value of learning outcomes without using LKPD based on a scientific approach is 45.00. While the average value of learning outcomes after being given treatment using LKPD based on a scientific approach is 80.00. From the analysis of learning outcomes, it shows that there are differences in learning outcomes before and after being given treatment using LKPD based on a scientific approach, when viewed from the average post-test learning outcomes is greater than the pre-test scores.